2018
DOI: 10.1016/j.bpsc.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Relationships Between Cognition and Brain Anatomy Across the Psychosis Spectrum

Abstract: General cognition and working memory with cortical volume deviations characterized more nonaffective psychoses. Alternatively, affective psychosis cases with general cognitive deficits had deviations in cortical surface area, perhaps accounting for heterogeneous findings across previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 92 publications
(104 reference statements)
1
16
0
Order By: Relevance
“…was largely driven by differences in cognitive performance between SZ/SZAD and ADHD/BD patients. This is consistent with a frontoparietal atrophy pattern being associated with cognitive performance in a transdiagnostic sample, and differentiated between SZ/SZAD and BD patients (73). Previous reports have also suggested similar cognitive deficit patterns among SZ, SZAD and BD patients, although the latter typically exhibited less severe deficits (3,(74)(75)(76)(77).…”
Section: Somatomotor Network Are Transdiagnostic Hubssupporting
confidence: 87%
“…was largely driven by differences in cognitive performance between SZ/SZAD and ADHD/BD patients. This is consistent with a frontoparietal atrophy pattern being associated with cognitive performance in a transdiagnostic sample, and differentiated between SZ/SZAD and BD patients (73). Previous reports have also suggested similar cognitive deficit patterns among SZ, SZAD and BD patients, although the latter typically exhibited less severe deficits (3,(74)(75)(76)(77).…”
Section: Somatomotor Network Are Transdiagnostic Hubssupporting
confidence: 87%
“…This finding is particularly important as the influence of the correlation strength on the stability of CCA results has been largely overlooked in previous studies. Indeed, many previous studies reported moderate CCCs-for example, 0.43 for a SVR of 8 (Lin et al, 2018) and 0.54 for a SVR of 9.97 (Rodrigue et al, 2018), or strong CCCs but at a relatively low SVR-for example, 0.87 for a SVR of 3.64 (Will et al, 2017) and 0.87 for a SVR of 4.61 (Smith et al, 2015), and the stability of their results may need to be reevaluated.…”
Section: The Stability Of Cca Results Is Affected By the Svr And The Correlation Strength Between Two Sets Of Variablesmentioning
confidence: 95%
“…We noticed that three subject measures (gender, height and weight) had very large loadings (Figures S2B and S3B), indicating that these three subject measures had major contributions to the first-mode correlation between brain imaging measures and subject measures. To further test whether the correlation strength between the two sets of variables also affects the stability of CCA results and whether the above observations also hold when there is only a moderate correlation between brain imaging measures and subject measures (Lin et al, 2018;Rodrigue et al, 2018), we removed these three subject measures and repeated all the above analyses to re-assess the stability of CCA results.…”
Section: Data Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that sparse methods are also often used in classification tasks, where they have been observed to provide better prediction but less stable weights (55,56), which indicates a trade-off between prediction and inference (55). Correspondingly, it has been suggested to consider weight stability as a criterion in sparsity parameter selection (55,57,58).…”
Section: Brain-behavior Associationsmentioning
confidence: 99%